Hidden Costs of Hospitalization After Firearm Injury: National Analysis of Different Hospital Readmission. Issue 5 (May 2018) - Rattan, Rishi; Parreco, Joshua; Namias, Nicholas; Pust, Gerd D.; Yeh, D. Dante; Zakrison, Tanya L.
Abstract : Objective: To compare the risk factors and costs associated with readmission after firearm injury nationally, including different hospitals. Background: No national studies capture readmission to different hospitals after firearm injury. Methods: The 2013 to 2014 Nationwide Readmissions Database was queried for patients admitted after firearm injury. Logistic regression identified risk factors for 30-day same and different hospital readmission. Cost was calculated. Survey weights were used for national estimates. Results: There were 45, 462 patients admitted for firearm injury during the study period. The readmission rate was 7.6%, and among those, 16.8% were readmitted to a different hospital. Admission cost was $1.45 billion and 1-year readmission cost was $131 million. Sixty-four per cent of those injured by firearms were publicly insured or uninsured. Readmission predictors included: length of stay >7 days [odds ratio (OR) 1.43, P < 0.01], Injury Severity Score >15 (OR 1.41, P < 0.01), and requiring an operation (OR 1.40, P < 0.01). Private insurance was a predictor against readmission (OR 0.81, P < 0.01). Predictors of readmission to a different hospital were unique and included: initial admission to a for-profit hospital (OR 1.52, P < 0.01) and median household income ≥$64, 000 (OR 1.48, P < 0.01). Conclusions: A significant proportion of the national burden of firearm readmissions is missed by not tracking different hospital readmission and its unique set of risk factors. Firearm injury-related hospitalization costs $791 million yearly, with the largest fraction paid by the public. This has implications for policy, benchmarking, quality, and resource allocation.